An Exploratory Study of Pronunciation Intelligibility in the Brazilian Learner’s English - Cruz, Neide Cesar (The ESPecialist, 2012)
This study aims at investigating the extent to which pronunciation errors at the segmental level – consonants, vowels, epenthesis and word stress – in the speech of Brazilian learners of English affect their intelligibility to native speakers. Quantitative and qualitative analyses revealed one main finding: out of the four error types investigated, word stress errors are likely to be a source of unintelligibility to native speakers who are familiar with the Brazilian accent.